Iceland: A Potential Destination for Incentive Travelers - Jóhanna Dagbjört Gilsdorf 1978- (2009)
This thesis explores the question of whether or not Iceland can be considered a good potential destination for the incentive travel market. The research concluded that Iceland is a good potential destination for the incentive travel market because of its unusual natural wonders, its ability to provide quality nature experiences to travelers, the close proximity of its location to the eastern United States, Canada and to Europe, not to mention the ease of travel within the country to desirable nature sites, the availability of good quality hotels and restaurants and its moderate climate. The research also concluded that there are areas Iceland needs to improve upon in order to make itself fully competitive in the incentive travel industry. This includes its delivery of services to clients, its need to be more aware of the cultural orientation of its clients and how best to deliver services effectively and efficiently, its need to provide more luxury accomodations for clients seeking exclusivity, and finally its need to offer some new activities, particularly in regards to special events and evening entertainment. The primary research for this project was done by conducting face to face interviews with seven travel professionals in Iceland who work or have worked with incentive travel clientele. The interviewees were both similar and different in their professional backgrounds which enabled them to approach the research questions from different perspectives. A supplementary questionnaire was used to obtain information from three incentive travel professionals located outside Iceland in different European countries, all of which make regular use of incentive travel business to Iceland. These agents offered insights to supplement those obtained from the face to face interviews as well as providing a perspective on the subject matter of the research from outside of Iceland.